THE EFFECT OF ESTAFET WRITING TECHNIQUE TO IMPROVE STUDENTS’ ABILITY IN WRITING PROCEDURE TEXT - ida yulianawati (Wiralodra English Journal, 2019)
This study aimed to know the effect of estafet writing to improve students’s ability in writing procedur text. Writing is one of the most important skill that should be mastered by students. But, sometimes the students have difficulties to express their writing because of many factors. The problem that faced by the students in writing are the students have problem in spelling, grammar, punctuation, uninterested media, do not have enough vocabulary so the students repeating the same words, and they often made grammatical errors. Estafet Writing is one of the active learning technique and also an innovative learning model in which one the students starts writing which is continued again one after another. It’s one of the techniques that is easy to learn and can be effective way to teach writing procedure text. To achieve the aim of the study, one class of a junior high school in Indramayu with 33 students was taken as the sample of the research. To help students to write procedur texts, estafet writing was used in the classroom. The data were obtained from pre-test and post-test. The result of this research showed that the students’ mean score in the pre test is 61.93 and the students’ mean score in post test is 81.78. This study shows that there is improvement of students’ ability in writing procedure text and the students give positive responses after being taught by using Estafet Writing Technique.